A cooperative approach to optimize the Printed Circuit Boards drill routing process using Intelligent Water Drops. (April 2015) - Srivastava, Praveen Ranjan
Graphical abstract: Abstract: Printed Circuit Boards (PCBs) are extensively used in the simplest electronic products. Inside, the PCB holes play a significant and important role. Holes through a PCB are typically drilled with small-diameter drill bits made of solid coated tungsten carbide. Drilling is done in a Printed Circuit Board to make holes at different points on it and is done by a robot drill to complete the whole assembly, which is frequently a bottleneck in an assembly line. Organizing and optimizing PCB drill route process is still open area of research. In this regards this paper uses the one of the newly developed heuristic technique i.e. Intelligent Water Drop (IWD) Algorithm to optimize the PCB drill routing process. The proposed method described here stands out for its ability to converge quickly using less number of iterations for the routing problem, limited use of computation resources and highly extensible for future development in robot type of application.